VPS39-deficiency observed in type 2 diabetes impairs muscle stem cell differentiation via altered autophagy and epigenetics - Cajsa Davegårdh (Nature Portfolio, 2021)
Insulin resistance and lower muscle strength in relation to mass are hallmarks of type 2 diabetes. Here, the authors report alterations in muscle stem cells from individuals with type 2 diabetes that may contribute to these phenotypes through VPS39 mediated effects on autophagy and epigenetics.